TiVo Hacks - Krikorian, Raffi (O'Reilly, 2011)
TiVo Hacks helps you get the most out of your TiVo personal video recorder. Armed with just a screwdriver and basic understanding of PC hardware (or willingness to learn), preeminent hackability awaits. This book includes hacks for changing the order of recorded programs, activating the 30-second skip to blaze through commercials, upgrading TiVo's hard drive for more hours of recording, use of TiVo's Home Media Option to remotely schedule a recording via the Web, log in to the serial port for command-line access to programming data, log files, closed-captioning data, display graphics on the TiVo screen, and even play MP3s.